MANAJEMEN PEMERINTAHAN DALAM PENGADAAN BARANG/JASA SECARA ELEKTRONIK (E-PROCUREMENT) DI PROVINSI RIAU TAHUN 2018 - Wiwit Eri Deswara (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
Electronic government procurement of goods/services (e-procurement) is an activity of obtaining goods/services by K / L / D / I whose process starts from planning to completion of all activities to obtain goods/services. These goods/service procurement activities are carried out using information technology and electronic transactions by statutory provisions. The problem in this study is that the government management has not been optimal for the procurement of government goods/services electronically (e-procurement) in Riau Province in 2018. The purpose of this study is to describe government management in the procurement of government goods/services electronically (e-procurement) in Riau Province in 2018. This research uses a qualitative approach with a descriptive research type. The research location is in the Bureau of Development Administration, Goods and Services Procurement which consists of the Procurement Service Unit (ULP) and Electronic Procurement Services (LPSE), the Riau Province PUPR Office as SKPD which is a budget user in the procurement of goods/services and the Inspectorate of Riau Province as government internal supervisory apparatus. Data were collected through informants purposively. Data collection techniques using interviews, and documentation study. Data analysis using qualitative analysis. The results of this study indicate that the obstacles found in the management of the procurement of goods/services in Riau Province lie in the quality of human resources, where the lack of officials who know the policies and regulations in force is caused by the rapid changes in the instruments of local government administration and changes frequently changes to central government regulations, lack of technical guidance and socialization, and not achieving ISO LPSE. These problems can affect functions in government management in the procurement of goods/services electronically (e-procurement) in Riau Province in 2018. Keywords: Management of Government, E-Procurement